The importance of multimodal CT examination in stroke mimics diagnosis: design of prospective observational multicentre study - Dvorníková, Kateřina; Kunešová, Veronika; Ely, Marcela; Ostrý, Svatopluk; Čábal, Martin; Reiser, Martin; Machová, Linda; Pavlínová, Markéta; Kondé, Adéla; Eliáš, Pavel; Jonszta, Tomáš; Havelka, Jaroslav; et al. (Frontiers in Neurology, 2024)
Introduction Non-contrast computed tomography (CT) and CT angiography are the gold standard in neuroimaging diagnostics in the case of suspected stroke. CT perfusion (CTP) may play an important role in the diagnosis of stroke mimics (SM), but currently, it is not a standard part of the stroke diagnostic procedure. The project is a multicentre prospective observational clinical research focused on refining the diagnostics of stroke and stroke mimics (SM) in hospital care. Aim This study aimed to evaluate the degree of specificity and sensitivity of multimodal CT (NCCT, CTA, and CTP) in the diagnosis of SM versus stroke. Methodology In this study, we will include 3,000 patients consecutively admitted to the comprehensive stroke centres with a diagnosis of suspected stroke. On the basis of clinical parameters and the results of multimodal CT and magnetic resonance imaging (MRI), the diagnosis of stroke and SM will be established. To clarify the significance of the use of the multimodal CT scan, the analysis will include a comparison of the blinded results for each imaging scan performed by radiologists and AI technology and a comparison of the initial and final diagnosis of the enrolled patients. Based on our results, we will compare the economic indicators and costs that would be saved by not providing inadequate treatment to patients with SM. Conclusion The expected outcome is to present an optimised diagnostic procedure that results in a faster and more accurate diagnosis, thereby eliminating the risk of inadequate treatment in patients with SM. Clinical trial registration clinicaltrials.gov, NCT06045455.